2015
DOI: 10.7554/elife.10222
|View full text |Cite
|
Sign up to set email alerts
|

Ternatin and improved synthetic variants kill cancer cells by targeting the elongation factor-1A ternary complex

Abstract: Cyclic peptide natural products have evolved to exploit diverse protein targets, many of which control essential cellular processes. Inspired by a series of cyclic peptides with partially elucidated structures, we designed synthetic variants of ternatin, a cytotoxic and anti-adipogenic natural product whose molecular mode of action was unknown. The new ternatin variants are cytotoxic toward cancer cells, with up to 500-fold greater potency than ternatin itself. Using a ternatin photo-affinity probe, we identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 45 publications
4
61
0
Order By: Relevance
“…6b ), which is currently in a phase I clinical trial for cancer therapy. We also observed potent antiviral effects of the elongation factor-1A (eEF1A) inhibitor ternatin-4 50 ( Fig. 6b ), which may suggest that the rate of translation elongation is critical for obtaining optimal levels of viral proteins.…”
Section: Mainmentioning
confidence: 81%
“…6b ), which is currently in a phase I clinical trial for cancer therapy. We also observed potent antiviral effects of the elongation factor-1A (eEF1A) inhibitor ternatin-4 50 ( Fig. 6b ), which may suggest that the rate of translation elongation is critical for obtaining optimal levels of viral proteins.…”
Section: Mainmentioning
confidence: 81%
“…However, it is not known if the translation elongation factors eEF1a and eEF2—which deliver aminoacyl-tRNAs to the ribosome and promote translocation, respectively—collaborate with Rqc2p to facilitate CAT-tail synthesis. Strikingly, we found that drugs targeting either eEF1a or eEF2 (didemnin variants ( Carelli et al, 2015 ) or sordarin ( Justice et al, 1998 ), respectively) had no effect on CAT tailing ( Figure 2C ). Because many canonical translation factors are GTPases, including eEF1a and eEF2, we also examined whether CAT tailing requires GTP hydrolysis.…”
Section: Resultsmentioning
confidence: 96%
“…Based on this observation, we propose a conserved mechanism (Schmeing et al., 2009) that didemnin B serves to increase the effective number of contacts between the GDP-bound G domain and domain 3 to prevent the inter-domain rotation that is necessary for eEF1A to release aa-tRNA and dissociate from the ribosome. Recently, didemnin B and ansatrienin B have been shown to compete with ternatin for binding to eEF1A (Carelli et al., 2015), and mutations in eEF1A Ala399, adjacent to the β15-β16 hairpin, were found to confer decreased sensitivity to didemnin B, ternatin, and another structurally unrelated natural product, nannocystin A (Carelli et al., 2015, Krastel et al., 2015). This suggests that these chemically diverse natural products share similar mechanisms of activity.…”
Section: Resultsmentioning
confidence: 99%